Karakterisasi Kopi Unggulan Indonesia Jenis Arabika Sangrai Medium To Dark Menggunakan Fourier Transform Infra Red - Nurul Mafazi; Zulkarnain Jalil; Elin Yusibani (Jurnal Teori dan Aplikasi Fisika, 2024)
This research was conducted to determine the chemical characteristics of Arabica Indonesia's coffee beans. Four types of coffee beans are taken as samples, i.e., from Toraja, Wamena, Kintamani, and Flores, then roasted to the medium to dark level around temperatures (213-215)°C within 9-13 minutes. Chemical properties testing in the form of identification of functional groups of coffee beans before and after the roasting process is carried out using FTIR. The results showed that the roasting process affects the functional groups and the appearance of flavor compounds in roasted coffee beans. There is the appearance of ether groups in the 1000-1300 cm-1 spectra region, aromatic acid groups in the 1680-1700 cm-1 spectra region, vinyl and lactone ester groups in the 1762-1780 cm-1 spectra region, 1724-1739 cm-1 aldehyde groups, 1740-1755 cm-1 aliphatic ester groups, 1705-1714 cm-1 aliphatic acid groups, and ketone groups in 1705-1725 cm-1 spectra region. Carbohydrates in the region of 1400-900 cm-1 are seen to have decreased transmittance. Keywords: medium to dark roasting, coffee, FTIR.